BEA MATERAI DI INDONESIA: Pengertian, Regulasi, Mekanisme, dan Permasalahan Penerapannya - Silfia, Sifa; Ahmad Zhuhri (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to examine how stamp duty is implemented in Indonesia, including its legal basis, functions, and scope, as well as the various issues that arise during its implementation, particularly in the digital age. The data sources consist of primary, secondary, and tertiary legal materials obtained through a literature review, and a descriptive-analytical normative legal approach was employed. The results of the study indicate that Stamp Duty serves two primary roles: a fiscal role to boost state revenue and a legal role to verify documents. Law No. 10 of 2020 brought significant changes due to technological advancements, such as the implementation of a single rate of Rp10,000 and the recognition of electronic stamps. However, in practice, numerous obstacles remain. These include a lack of public awareness, technical issues with e-Stamps, and deficiencies in infrastructure and regulations. Additionally, the implementation of Stamp Duty impacts taxpayer compliance levels; simplifying the system and increasing public outreach can improve compliance. Consequently, to optimize the implementation of Stamp Duty in the future, enhanced education, strengthened legislation, and the development of an integrated digital system are required.